Penggunaan Sufiks-An Pada Tajuk Rencana Harian Surat Kabar Kompas Sebagai Bahan Pembelajaran Bahasa Indonesia Di SMK Muhammadiyah 6 Gemolong - Muvida, Vera; , Drs. Yakub Nasucha, M.Hum (2016)
The aim of study are (1) knowing how to use suffix -an in editorial Kompas daily newspaper as learning material of Indonesian lesson at SMK Muhammadiyah 6 Gemolong, (2) Accesing how the notion/ meaning of the use of suffix -an in editorial Kompas daily newspaper as learning material used descriptive qualitative method. The data in this study is an editorial containing the use of suffix -an. The data source of this research is Kompas daily newspaper. Data collection techniques used the see and record technique. Data were analyzwd using agih technique. The result of this study (1) associated with the use of suffix -an at Kompas daily newspapers can be found as many as 36 data. (2) to do with the notion / meaning of the use of suffix -an on editorial detailed Kompas daily newspaper can be explained that a) the circumstances relating / size / each has 7 data, b) resembles / clone can be found 1 record, c ) notion can be found data 14, d) the object of work can be found 10 data, e) the results of the work can be found 5 Data, f) tool to perform the data is not found. The results of this study have implications for learning the Indonesian language as a form of teaching materials for students in SMK. Keywords: affixation, suffixes, tajukrencana, newspapers.